A Preoperative Nomogram for the Prediction of High-Volume Central Lymph Node Metastasis in Papillary Thyroid Carcinoma - Lin, Peiliang; Liang, Faya; Ruan, Jingliang; Han, Ping; Liao, Jianwei; Chen, Renhui; Luo, Baoming; Ouyang, Nengtai; Huang, Xiaoming (Frontiers in Endocrinology, 2021)
Background High-volume lymph node metastasis (HVLNMs, equal to or more than 5 lymph nodes) is one of adverse features indicating high recurrence risk in papillary thyroid carcinoma (PTC) and recommended as one of the indications of completion thyroidectomy for the patients undergoing thyroid lobectomy at first. In this study, we aim to develop a preoperative nomogram for the prediction of HVLNMs in central compartment in PTC (cT1-2N0M0), where preoperative imaging techniques perform poor. Methods From Oct. 2016 to Apr. 2021, 423 patients were included, who were diagnosed as PTC (cT1-2N0M0) and underwent total thyroidectomy and prophylactic central compartment neck dissection in our center. Demographic and clinicopathological features were recorded and analyzed using univariate and multivariate logistic regression analysis. A nomogram was developed based on multivariate logistic regression analysis. Results Among the included patients, 13.4% (57 cases) were found to have HVLNMs in central compartment. Univariate and multivariate logistic regression analysis showed age (35 years), BRAF with V600E mutated, nodule diameter, and calcification independently predicted HVLNMs in central compartment. The nomogram showed good discrimination with AUC of 0.821 (95% CI, 0.768–0.875). Conclusion The preoperative nomogram can be used to quantify the probability of HVLNMs in central compartment and may reduce the reoperation rate after thyroid lobectomy.